MANAGEMENT CONSULTING OF THE AGRICULTURAL KNOWLEDGE AND INNOVATION SYSTEM (AKIS) IN UKRAINE - Krykunenko, Kateryna; Zhemoyda, Oleksandr; Zikranets, Mykola (Socio-economic relations in the digital society, 2024)
European Integration of Ukraine in the Ukrainian aspiration to join the European Union (EU) entails rapprochement with the Common Agricultural Policy (CAP) of the EU. One important element for the attainment of CAP objectives is a strong Agricultural Knowledge and Innovation System (AKIS). This article analyses the describable potential of the AKIS framework in the pre-accession phase of Ukraine. We review current AKIS components, their key issues identified, and strategies to reinforce them. Using a literature review, policy document analysis and expert interviews with key stakeholders that shape the current landscape of Ukrainian agriculture, the analysis was constructed. The results revealed that while UE is well placed as far as AKIS functionality is concerned, there are considerable areas that require improvements. Enhancing synergies between research, extension and farmers, encouraging co-creation of knowledge and harnessing digital technologies are some key steps. An effective AKIS standing behind the Ukrainian agriculture can make the country more productive, sustainable, and competitive improving its compatibility with the EU’s CAP mechanisms.